A Critical Investigation into the Existence of Circulating Platelet Aggregates - Saniabadi, A R; Lowe, G D O; Madhok, R; Spowart, K; Shaw, B; Barbenel, J C; Forbes, C D (Thrombosis and Haemostasis, 1986)
By a method of counting single platelets in diluted whole blood, platelet aggregates were quantified ex-vivo. Four groups: 20 thrombotic patients, 10 non-thrombotic patients, 10 healthy old controls and 10 healthy young controls were included in the study. Using a 19 gauge needle, with and without tubing, venous blood was taken into buffered EDTA, as a disaggregating agent and buffered EDTA-formalin, as the fixative. The amount of platelet aggregates quantified was affected by the quality of venepuncture or the rate of blood flow through the needle, but was unaffected by the presence of the tubing. There was no statistically significant difference between the four groups, in terms of the platelet aggregates quantified, but scanning electron microscopy revealed the presence of irreversible aggregates, composed of platelet red and white blood cells, in the blood of a greater number of thrombotic patients than non-thrombotic or healthy controls. Platelet aggregates were also quantified in aliquots of platelet rich plasma, and were found to be significantly greater than the corresponding values in whole blood. The difference appeared to be due to increased viscosity of the plasma, induced by the fixative which reduces platelet mobility during centrifugation. It is concluded that the platelet aggregates which disaggregate in bufffered EDTA may represent an artifact of blood collection; the irreversible aggregates are suspected to represent the in vivo circulating aggregates.
Keywords: Circulating platelet aggregates; Platelet count ratio; Irreversible aggregates; White blood